SOCIO-ECONOMIC BACKGROUND OF WOMEN IN SRIKAKULAM DISTRICT - B., Rajesh (International Journal of Psychosocial Rehabilitation, 2020)
The study examines the socio-economic background of women in Andhra Pradesh with reference to a study on DWACRA women in Srikakulam District. This paper is divided into five sections A. Personal data it covers the classification of the respondents by age, religion, caste, marital status, educational background, occupation and area of residence B. Household composition, which includes total number of family members and number of dependents C. Migratory character deals with type of migration, reasons for migration and periodicity of visit to native place D. Household income and expenditure includes monthly income of the respondents, monthly household income, monthly savings and expenditure E. Assets and liabilities cover the nature of the residential accommodation, ownership of household assets and productive assets, and sources of loans.